First-principles study of spin-polarized electronic band structures in ferromagnetic Zn1-xTMxS (TM = Fe, Co and Ni) - Saeed, Y.; Nazir, S.; Ali H. Reshak, Al-Jaary; Shaukat, A. (Elsevier B. V., 2010)
Link to publisher’s homepage at http://www.elsevier.com/